Transcriptome and volatile compounds analyses of floral development provide insight into floral scent formation in Paeonia lactiflora ‘Wu Hua Long Yu’ - Zhao, Qian; Zhang, Min; Gu, Lina; Yang, Zihan; Li, Yuqing; Luo, Jianrang; Zhang, Yanlong (Frontiers in Plant Science, 2024)
Herbaceous peony (Paeonia lactiflora) is a well-known ornamental plant in China, celebrated for its beautiful flowers that can emit fragrances. However, exact molecular mechanisms governing synthesis of floral volatiles within herbaceous peony remain unclear. To address this gap in knowledge, our study focused on analyzing the transcriptome and the levels of floral volatile compounds in P. lactiflora 'Wu Hua Long Yu' at different stages of flower development. Using gas chromatography-mass spectrometry (GC-MS), we obtained eighteen major volatile compounds, with monoterpenes being the dominant components among them. Our transcriptome analysis, based on pooled sequencing data, revealed the most differentially expressed genes (DEGs) existed between stages S1 and S3 of flower development. Among these DEGs, we identified 89 functional genes associated with the synthesis of volatile monoterpenes, with 28 of these genes showing a positive correlation with the release of monoterpenes. Specifically, key regulators of monoterpene synthesis in herbaceous peony appear to be 1-deoxy-D-xylulose 5-phosphate synthase (DXS), geranyl pyrophosphate synthase (GPPS), and terpene synthase (TPS). Additionally, our study identified some transcription factors (TFs) that may be involved in the biosynthesis of monoterpenes. These discoveries offer invaluable illumination into the intricate molecular underpinnings orchestrating the generation of floral fragrances in herbaceous peonies, and they offer a foundation for further research to identify and utilize candidate gene resources for this purpose.